TRENDS OF ALTERATION OF EDUCATIONAL PROGRAMS OF FOREIGN LANGUAGE TRAINING OF PHILOLOGY MASTERS (at the beginning of the 21st century) - Sultanova, Natalia; Korniienko, Mariia (Mountain School of Ukrainian Carpaty, 2022)
The aim of the study is to to reveal the main trends of alteration of programe provision of foreign language training of philology masters at the beginning of the 21st century. Relevance of the problem is determined by transformational changes in educational and professional programs in accordance with national interests and individual needs in the context of the European educational space. The article covers the main problems and prospects for the development of master's education in Ukraine in general and the foreign language training of philology masters in particular. Constructive ideas of scientists regarding the development of educational professional programs at the master's level of various profiles are highlighted. First of all, it is about: a) innovative orientation of training specialists; b) scientific and research component of educational and training programs; c) variable part of educational plans; d) cross-cultural nature of educational content; e) close cooperation of programe provision developers with employers and e) European orientation and value meaning of educational activities. The authors outline the main trends in the development of programe provision of the foreign language training of philology masters at the current stage, among which they point to the standardization of the content and results of educational activities; differentiation of the content of education and forms of control over its results at different levels of higher education; competence orientation and personal orientation of training specialists with higher education; correlation between the educational and professional program and programs of academic disciplines; variability of the content of higher education taking into account European, national and individual needs and opportunities. European educational and cultural integration is considered an indispensable condition for effective transformational changes of programe provision of foreign language training of philology masters in Ukraine.